2017
DOI: 10.1037/xlm0000318
|View full text |Cite
|
Sign up to set email alerts
|

Reading sky and seeing a cloud: On the relevance of events for perceptual simulation.

Abstract: Previous research has shown that processing words with an up/down association (e.g., bird, foot) can influence the subsequent identification of visual targets in congruent location (at the top/bottom of the screen). However, as facilitation and interference were found under similar conditions, the nature of the underlying mechanisms remained unclear. We propose that word comprehension relies on the perceptual simulation of a prototypical event involving the entity denoted by a word in order to provide a genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 72 publications
(118 reference statements)
2
40
0
Order By: Relevance
“…Single-category cues allow participants to establish a spatial reference frame that remains constant across the experiment, creating a more consistent stimulus-response mapping across trials. This consistent mapping renders responding more efficient, thereby eliminating the interference effect and sometimes producing facilitation instead (Gozli et al, 2013;Ostarek & Vigliocco, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-category cues allow participants to establish a spatial reference frame that remains constant across the experiment, creating a more consistent stimulus-response mapping across trials. This consistent mapping renders responding more efficient, thereby eliminating the interference effect and sometimes producing facilitation instead (Gozli et al, 2013;Ostarek & Vigliocco, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Following Petrova et al (in-press), we included only studies in which the visual target was abstract and unrelated to the linguistic cue (e.g., X or O, ■ or •). This excludes studies in which the visual target was a familiar object (Estes et al, 2015, Experiments 1 and 2;Ostarek & Vigliocco, 2017), because familiar objects have their own spatial and semantic associations that affect responding to targets at different locations (Ostarek & Vigliocco, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The evidence for the automatic mental simulation of touch is perhaps stronger, with texture regions of the brain activated when reading and understanding texture-related sentences (Lacey et al, 2012). In order to critically assess the automaticity of mental simulations, future studies could focus on the time-course of activations (e.g., Ostarek & Vigliocco, 2017), or use tasks less likely to elicit strategic mental imagery and more akin to everyday language use, such as narrative comprehension (Kurby & Zacks, 2013;Willems & van Gerven, 2018).…”
Section: Assessing the Evidencementioning
confidence: 99%
“…The relevance of space has been investigated for concepts that are typically experienced high or low in space. Studies show that speed of responses to words are affected by whether they are presented in a spatially congruent (e.g., hat in high position) or incongruent (e.g., hat in low position) positions (e.g., Estes, Verges, & Barsalou, 2008;Ostarek & Vigliocco, 2017). Instead of vertical space, Speed and Majid (2017a) examined mental simulation of proximal and distal space.…”
Section: Crossmodal Compensationmentioning
confidence: 99%
“…Numerous studies have shown that processing up/down words can influence performance at visual tasks involving compatible vs. incompatible location (Estes, Verges, & Adelman, 2015;Estes, Verges, & Barsalou, 2008;Gozli, Chasteen, & Pratt, 2013;Ostarek & Vigliocco, 2017). Behavioral work has established that processing up/down words enhances spatial attention to the compatible location which often leads to facilitated detection and identification of visual targets in the primed location (Dudschig, Lachmair, de la Vega, De Filippis, & Kaup, 2012;Gozli et al, 2013;Ostarek & Vigliocco, 2017).…”
Section: Introductionmentioning
confidence: 99%